PENGARUH BULLYING TERHADAP HASIL BELAJAR SISWA PADA TEMA LINGKUNGAN SAHABAT KITA KELAS V SD NEGERI 173416 POLLUNG - Zainal Dominikus Siregar; Reflina Sinaga; Sumarlin Mangandar Marianus (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to determine the effect of student bullying on student learning outcomes in class V SD Negeri 173416 Pollung. The population of this study were all students of class V SD Negeri 173416 Pollung totaling 62 students. The sample used was 62 students to be used as samples in this study. In this study, researchers used a survey type quantitative method. To test the hypothesis using the product moment correlation t test. The results showed that student bullying had an average of 85 with sufficient category and learning outcomes had 68.72 in the less category. This is supported by the results of the t test hypothesis testing where the value of t_count > t_table is 1,714 > 1,669 then Ha is accepted, that is, there is an effect of student bullying. There is a significant relationship between student bullying and student learning outcomes on the theme of our friend's environment, sub-theme of humans and the fifth grade environment of SD Negeri 173416 Pollung, Humbang Hasundutan Regency.